Efficacy and Safety of Neoadjuvant Targeted Therapy vs. Neoadjuvant Chemotherapy for Stage IIIA EGFR-Mutant Non-small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Chen, Dong; Jin, Zixian; Zhang, Jian; Xu, Congcong; Zhu, Kanghao; Ruan, Yuhang; Zhang, Bo; Chen, Baofu; Shen, Jianfei (Frontiers in Surgery, 2021)
Purpose: The role of targeted therapy in the neoadjuvant field of stage IIIA epidermal growth factor receptor (EGFR) mutation-positive non-small cell lung cancer (NSCLC) is still controversial. We sought to evaluate the efficacy and safety of neoadjuvant targeted therapy (NTT) with neoadjuvant chemotherapy (NCT) used as a benchmark comparator. Methods: A systematic search was conducted in four databases (Pubmed, Cochrane Library, Embase, CNKI) for eligible studies on NTT published before October 2020. The primary endpoints were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and grade 3/4 adverse events (AEs). Statistical analysis and bias assessment were performed by RevMan 5.3. Results: A total of 319 patients, including 3 randomized controlled trials and 2 non-randomized controlled trials, were included in the meta-analysis. Perform the second subgroup analysis after excluding 2 non-randomized controlled trials. The meta-analysis reveals that, for EGFR mutation-positive stage IIIA NSCLC patients, compared with NCT, NTT can significantly increase ORR (relative risk [RR]:1.70, 95% confidence interval [CI]:1.35–2.15; subgroup-RR:1.56, 95% CI 1.23–2.0) and significantly reduce grade 3/4 AEs (RR:0.5, 95% CI 0.34–0.75; subgroup-RR: 0.53, 95% CI 0.26–1.08). The OS of the NTT arm is slightly higher, but the difference is not significant (hazards ratio [HR]: 0.74, 95% CI: 0.43–1.27; subgroup-HR: 0.64 95% CI 0.40–1.03). No difference in PFS was found (HR: 0.81, 95% CI 0.27–2.44). Conclusion: In neoadjuvant setting, targeted therapy has a definitive effect on patients with EGFR mutation-positive stage IIIA NSCLC and is even better than chemotherapy in terms of toxicity and tumor response rate. Systematic Review Registration: PROSPERO, identifier CRD42021221136.